Dampak Penggunaan Jenis Pupuk Terhadap Pendapatan Petani Padi Sawah di Kabupaten Batanghari - Rizki Gemala Busyra (Jurnal MeA (Media Agribisnis), 2022)
Batanghari Regency is one of the regencies in Jambi Province that has a  potential for the development of lowland rice commodities. Rice farming in Batanghari Regency consists of organic and inorganic rice. Organic rice is a farming technique using fertilizer  (compost and organic fertilizers) that can be broken down by decomposer organisms. The continuous use of chemical fertilizers and pesticides on agricultural land results in a decrease in the structure and composition of nutrients and soil fertility which indirectly affects the level of production. The decrease in the level of production will be followed by a decrease in the level of farmers' income which will have an impact on the decrease in farmers' income. The purpose of this study was to determine the impact of using organic fertilizers on lowland rice plants on farmers' income in Batanghari Regency. The results showed that simultaneously the independent variables had a significant effect on the income of lowland rice farmers. Partially, rice production, fertilizer costs, pesticide costs and types of fertilizers had a significant effect on the income of lowland rice farmers, while the level of education did not significantly affect the income of lowland rice farmers in Batanghari Regency. The type of fertilizer had a significant effect on the income of lowland rice farmers, so that the income of rice farmers who use organic fertilizers was higher than the income of rice farmers who used inorganic fertilizers.